KOLABORASI DIGITAL MARKETING DALAM MENINGKATKAN KINERJA UMKM - Nuriza, Alsya; Zulva, Tiara Zahara; Nafisal Hakim, Nazla (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2024)
Collaboration is one of the most significant things that can help MSMEs perform better, especially when it comes to digital marketing. This study aims to identify and elucidate the role that digital marketing partnership plays in enhancing MSMEs' performance in Sukabumi Regency. The MSME players in Sukabumi Regency, which has 363,175 residents, are the subject of this research. This study's methodology is descriptive and quantitative. To generate a sample of 100 respondents, the sampling technique employed in this study was web.raosoft.com sample size with an error rate of 10%. Respondents were given questionnaires in the form of questions as part of the data collection approach used in this study. This study's analysis technique was simple linear regression analysis. The study's findings demonstrated that, with a 69.8% influence from digital marketing and a 30.2% influence from other factors, MSMEs' sustainability is positively and significantly impacted by this strategy.